Case Report: Benign Multicystic Peritoneal Mesothelioma - Nurettin Boran; Yetkin Karasu; Taner Turan; Faruk Demir; Gökhan Tulunay; Faruk Köse (Medical Network, 2011)
Benign multicystic peritoneal mesothelioma (BMPM) is a rare tumor of unknown pathogenesis that occurs mainly in women in their reproductive ages and mostly diagnosed intraoperatively. In this paper, a case was summarized with pelvic mass which was handled as an ovarian cancer preoperatively. A 40 year old woman admitted to gynecologic oncology unit due to pelvic pain. On bimanual gynecologic examination a unilateral, semi-fixated pelvic mass in the right adnexial region was palpated. She had no medical history of malignancy. On pelvic ultrasound in the right adnexial region a multiseptated mass was reported. Ca-125 level was 178.2 IU/ml. On gross examination during operation, there was a thin walled multicystic pelvic mass adherent to posterior cul de sac, rectal serosa, and right pelvic wall. Pathologists' first impression was that mass was not containing any malignant component on frozen sections. Carefull resection of pelvic mass, total abdominal hysterectomy, right salphingooophorectomy and appendectomy performed. The final pathologic diagnosis was BMPM with parafine blocks. In conclusion BPMP is a rare benign cystic tumor which can be easily misdiagnosed as an ovarian cancer preoperatively. Intraoperative findings and appearence of the mass may mimic malignancy. For that reason frozen section examination will prevent overtreatment.